Serum Free Fatty Acids Independently Predict Adverse Outcomes in Acute Heart Failure Patients - Yu, Yi; Jin, Chunna; Zhao, Chengchen; Zhu, Shiyu; Meng, Simin; Ma, Hong; Wang, Jian'an; Xiang, Meixiang (Frontiers in Cardiovascular Medicine, 2021)
Background: Perturbation of energy metabolism cardiac dysfunction, serving as a potential therapeutic target in congestive heart failure. Although circulating free fatty acids (FFAs) are linked to insulin resistance and risk of coronary heart disease, it still remains unclear whether circulating FFAs are associated with the prognosis of patients with acute heart failure(AHF). Methods: This single-center, observational cohort study enrolled 183 AHF patients (de novo heart failure or decompensated chronic heart failure) in the Second Affiliated Hospital, Zhejiang University School of Medicine. All-cause mortality and heart failure (HF) rehospitalization within 1 year after discharge were investigated. Serum FFAs were modeled as quartiles as well as a continuous variable (per SD of FFAs). The restricted cubic splines and cox proportional hazards models were applied to evaluate the association between the serum FFAs level and all-cause mortality or HF rehospitalization. Results: During a 1-year follow-up, a total of 71 (38.8%) patients had all-cause mortality or HF rehospitalization. The levels of serum FFAs positively contributed to the risk of death or HF rehospitalization , which was not associated with the status of insulin resistance. When modeled with restricted cubic splines, the serum FFAs increased linearly for the incidence of death or HF rehospitalization. In a multivariable analysis adjusting for sex, age, body-mass index, coronary artery disease, diabetes mellitus, hypertension, each SD (303.07μmol/L) higher FFAs were associated with 29% higher risk of death or HF rehospitalization (95% confidence interval, 5% - 58%). Each increasing quartile of FFAs was associated with differentially elevated hazard ratios for death or HF rehospitalization of 1 (reference), 1.71 (95% confidence interval, [0.81, 3.62]), 1.45 (95% confidence interval, [0.68, 3.08]), and 3.26 (95% confidence interval, [1.59, 6.68]), respectively. Conclusion: Serum FFA levels at admission among patients with AHF were associated with an increased risk of adverse outcomes. Additional studies are needed to determine the causal-effect relationship between FFAs and acute cardiac dysfunction and whether FFAs could be a potential target for AHF management.